PENINGKATAN AKTIVITAS BELAJAR EKONOMI SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION DI KELAS X – 2 SMA NEGERI 12 MEDAN - RISMAWATI PURBA (JURNAL HANDAYANI PGSD FIP UNIMED, 2014)
ABSTRACT The goal of research is viewing the student activity on economy lesson in class of X – 2 SMA Negeri 12 Medan by applicated the cooperative learning model type Group Investigation. The subject of research is taken in class of X – 2 SMA Negeri 12 Medan by the amount of students is 46 students. The student activity data accord the observation in cycle I among others writing / reading (45,45%), doing worksheet (24,09%), asking for student (11,82%), asking for techer (11,82%), and not relevant with teaching – learning process (6,82%). The student activity data accord observation in cycle II among others writing / reading (21,58%), doing worksheet (8,75%), asking for student (17,92%), asking for teacher (7,08%) and not relevant with teaching – learning process (1,67%). By using the learning model of Group Investigation  is gotten the student learning outcomes form the cylce to next cycle occur the increasing. On cylce I is shown the individual complete of 24 student by classical completeness a much of 52,17%. On cycle II is shown indiviudual complete of 41 student by classical completeness is 89,13%. The student outcomes by applicated the cooperative learning model type Group Investigation in first formative and second formative is shown the average of result is 69,9 and 92,4 and from that data is complete / graduate appropiate with Economy Minimal Criteria Completeness (CCM).   Keywords: Cooperative Learning Model Type Group Investigation, Learning Activitity, Learning Outcomes